Plasma treatment of carbon fibres and glass-fibre-reinforced polyesters at atmospheric pressure for adhesion improvement. (1st January 2014) - Kusano, Yukihiro; Andersen, Tom L.; Toftegaard, Helmuth L.; Leipold, Frank; Bardenshtein, Alexander; Krebs, Niels
Atmospheric pressure plasma treatment is useful for adhesion improvement, because cleaning, roughening and addition of polar functional groups can be expected at the surfaces. Its possible applications in the wind energy industry include plasma treatment of fibres and fibre-reinforced polymer composites before assembling them to build wind turbine blades. In the present work, unsized carbon fibres are continuously treated using a dielectric barrier discharge plasma in helium at atmospheric pressure, and carbon fibre reinforced epoxy composite plates are manufactured for the mechanical test. The plasma treatment improved fracture toughness, indicating that adhesion between the fibres and the epoxy was enhanced by the treatment. In addition, glass-fibre-reinforced polyester plates are treated using a gliding arc and an ultrasound enhanced dielectric barrier discharge, improving the wettability and/or the adhesive strength with a vinylester resin.